The participation of a specialist during interrogation - Яремчук, Вікторія Олегівна (Problems of legality, 2016)
This report is devoted to studying certain aspects of expert involvement in conducting common investigative acts including interrogation. We carried out an analysis of rules of procedure, governing issues of specialist involvement in interrogation. We also tried to highlight pressing issues related to specialist involvement in interrogation. Issues of specialist involvement in interrogation previously came into focus in the works of the following scholars: A. N. Zynyn, A. N. Ekymovskaia, I. M. Komarov, V. Е. Konovalova, I. V. Pyroh, V. V. Tsyrkal, V. Y. Shepіtko et al. This report aims at analyzing topical issues of specialist involvement in interrogation from the perspective of interaction with the investigator. This report studies the norms of the Code of Criminal Procedures of Ukraine concerning procedural regulation of specialist involvement in interrogation. We reviewed the issue of specialist involvement in interrogation by the defense team as well as specialist involvement in interrogation via videoconference. We also suggested classification of types of specialists involved in interrogation. We characterized forms and functions of specialist activities. We reviewed issues of specialist consulting and information assistance as one of the most common forms of professional assistance during interrogation.